2021
DOI: 10.1111/cpr.13024
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analyses hinted at augmented T helper 17 cell differentiation and cytokine response as the central mechanism of COVID‐19–associated Guillain‐Barré syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
18
0
1
Order By: Relevance
“…It should also be considered that group 3 innate lymphoid cells (ILC3s) and mucosal-associated invariant T (MAIT) cells are highly activated in patients with COVID-19, irrespective of the course of the disease, and express high levels of proinflammatory cytokines such as IL-17A, suggesting their possible involvement in COVID-19 immunopathogenesis [61] , [62] . Finally, bioinformatic analyses to delineate the potential genetic crosstalk between COVID-19 and Guillain-Barré syndrome have suggested that aberrant Th17 cell differentiation could represent a possible mechanism by which SARS-COV-2 can increase the risk of the autoimmune peripheral nervous disease [63 ] . Taken together, these findings underline a key role of IL-17A in COVID-19 and likely could pave the way to novel therapeutic approaches based upon IL-17A blockage by biological drugs that are already available [19] , [64] .…”
Section: Il-17a As a Rheostat Of Covid-19 Immune Responsementioning
confidence: 99%
“…It should also be considered that group 3 innate lymphoid cells (ILC3s) and mucosal-associated invariant T (MAIT) cells are highly activated in patients with COVID-19, irrespective of the course of the disease, and express high levels of proinflammatory cytokines such as IL-17A, suggesting their possible involvement in COVID-19 immunopathogenesis [61] , [62] . Finally, bioinformatic analyses to delineate the potential genetic crosstalk between COVID-19 and Guillain-Barré syndrome have suggested that aberrant Th17 cell differentiation could represent a possible mechanism by which SARS-COV-2 can increase the risk of the autoimmune peripheral nervous disease [63 ] . Taken together, these findings underline a key role of IL-17A in COVID-19 and likely could pave the way to novel therapeutic approaches based upon IL-17A blockage by biological drugs that are already available [19] , [64] .…”
Section: Il-17a As a Rheostat Of Covid-19 Immune Responsementioning
confidence: 99%
“…Th17 cells are known to play an important role in the pathogenesis of various immune-mediated diseases such as rheumatoid arthritis, multiple sclerosis, and inflammatory bowel disease ( 29 ). In a recent bioinformatics analysis; Th17 cell differentiation and cytokine response was identified as an important process connecting COVID-19 to GBS ( 30 ). In our study, transferrin and albumin levels, which are negative acute phase reactants, were found to be significantly lower in the post-COVID-19 GBS group compared to the non-COVID-19 GBS group; D-dimer levels were found to be high.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine storm resulting from viral disturbance of the immune system could be why patients with COVID-19 are predisposed to neuropathies like GBS. In particular, Li et al recently revealed the underlying pathophysiology of GBS in COVID-19 by conducting bioinformatics analyses [ 93 ]. The genetic crosstalk between COVID-19 and GBS they observed shows the pivotal role of Th17 cells in increasing the risk of GBS in COVID-19 patients [ 93 ].…”
Section: Indirect Systemic Damagementioning
confidence: 99%